Epidemiology of onychomycosis in Italy: prevalence data and risk factor identification. Issue 11 (28th September 2015) - Papini, Manuela; Piraccini, Bianca Maria; Difonzo, Elisa; Brunoro, Andrea
Summary: The prevalence of onychomycosis differs according to geographic area and over time and is influenced by several factors. The epidemiology of onychomycosis in Italy is still unclear. To evaluate the prevalence of onychomycosis in a representative sample of the Italian population a group of Dermatologists and General Practitioners carried out an observational survey on the patients coming to their office during a 1‐month period. Any patient with skin or systemic disease giving their consent was enrolled. Demographic characteristics, comorbidities, lifestyles, history of previous mycosis, clinical aspects of onychomycosis and mycological evaluation were studied. A total of 8331 patients (56.7% female and 43.3% male) were evaluated. More than half of them were aged ≥46 years. Onychomycosis was diagnosed in 14.2% of patients. Big toe and thumb were the most frequently affected nails. Onychomycosis was moderate‐severe in 74.1% of the cases. Mycological tests were positive in 81.3% of the cases. Dermatophytes were found in 76.6% of the cases, yeasts in 17.2% and moulds in 6.3%. Risk factors and/or comorbidities were present in 68.2% of the cases. This survey showed a 14% prevalence of onychomycosis in the evaluated population. The main risk factors were previous onychomycosis, diabetes, hallux valgus and use of occlusive footwear.